Amicus curiae para quê?: o papel do amicus curiae na função jurisdicional e seus desafios à luz do novo Código de Processo Civil de 2015. - Rocha, Victor Yuri Brederodes da (2018)
In democratic societies in the world that are governed by a constitutional and notable system as a constitutional jurisdiction for constitutionality control intends a question of legitimacy for a government as decisions of broad social impact for Judges without democratic representativeness. The present work has as scope an analysis of the institute of the amicus curiae, as a tool to foment the process of constitutional interpretation within the judiciary and the impacts of the new Civil Procedure Code of 2015 (Law No. 13.105 / 2015) on this institute. To do so, it will be worth studying the origin of the institute, its expression in other legal systems on comparative law and its evolution in Brazilian law.